Public-private partnership models for rehabilitation service delivery: A scoping review - Senzelwe M. Mazibuko; Thayananthee Nadasan; Pragashnie Govender (AOSIS, 2023)
Background: Public-private partnership (PPP) for the delivery of health services is known to improve access to healthcare, yet little is known about its utilisation for rehabilitation services, particularly in sub-Saharan Africa (SSA). Objectives: As a first step to generating evidence to develop a PPP model for physiotherapy service delivery in South Africa, our study mapped and described available research evidence on PPP models for rehabilitation services in the global literature. Method: The Arksey and O'Malley framework guided our scoping review. Published research on rehabilitation and PPP was searched in five databases from 2000 to August 2022 using keywords, Medical Subject Headings (MeSH) and Boolean terms. Two reviewers independently completed the titles, abstracts and full-text screening of the articles and data extraction from the included articles. A narrative synthesis was conducted, and summaries of the findings are reported. Results: Nine articles were included from a total of 137 obtained from the evidence searches. Of these, five were from Australia and the others from Hong Kong, Denmark, Bangladesh and the Netherlands. All the included articles showed evidence of PPP models for physiotherapy service delivery. Conclusion: Our study suggests that PPP models for physiotherapy service delivery exist, particularly in high-income countries (HICs). It also highlights limited research in low- and middle-income countries (LMICs). Clinical implications: There is a need for primary studies to generate further evidence and develop innovative PPP models for rehabilitation services for the populations who need them most as part of efforts towards improving access to healthcare in LMICs.